The concept of comprehensive codification of the legislation on information in Ukraine - Татарникова, Кристина Геннадіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article offers the author's position regarding the concept of a comprehensive codification of thelegislation on the information. As the results of research it is concluded that further regulation of socialrelations in the legislative process should dominate only the concept of comprehensive codification of thelegislation on information.